Diseño de un modelo de gestión del talento humano para el GAD Municipal del cantón Salcedo. - Torres Barriga, Erika Vanessa (2014)
The present research study had led us to pose like a proposal the design of a Model of Human Resource Management for Autonomous Decentralized Municipal Government of Salcedo city, this has an objective, to provide tools to improve existing processes and implement new trends in subsystems of human talent management, allowing to increase the productivity and job performance of employees and workers of the institution and therefore to develop in a suitable environment and obey all requirements emitting from control entities. Of this way it´ll help to the Head of Human Resource in coordination with the Office of Organizational Development to have a starting point to improve the management with respect to administrative and operational staff, ensuring better conditions in his position and post to perform; since the admissions staff is integrating skilled people to develop in their workplace, which will receive induction, security, and occupational health; they´ll be follow and at the end the develop test.